The Use of Artificial Intelligence in Learning: Primary School and Prospective Teachers' Perceptions - Alfian Fawaidil Wafa; Dany Wijaya Kesuma (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2025)
This research was conducted to analyze exactly how teachers and prospective elementary school teachers perceive the use of Artificial Intelligence (AI) in the learning process. This research aims to be a means of recommending the implementation of optimal use of AI at the primary education level. This study uses a quantitative approach with a descriptive research design through a survey method. Data were taken from 46 respondents of teachers and prospective elementary school teachers in the city of Malang who were selected using voluntary sampling techniques. Descriptive statistical analysis shows that, in general, respondents gave predominantly positive responses to AI integration, with average perception scores ranging from 19.17 to 21.46, indicating a tendency to agree. Key findings reveal a perception paradox: on the one hand, 73.9% of teachers believe AI can improve teaching effectiveness through personalisation and administrative efficiency; on the other hand, there is significant concern (69.6% agree) that AI has the potential to reduce essential social interaction between teachers and students. In addition, the main obstacles identified are the lack of teacher literacy and limited technological infrastructure in schools. Therefore, this study recommends the need for structured professional training and improved digital infrastructure as prerequisites for balancing the functional benefits of AI with the maintenance of the humanistic pedagogical role of teachers in primary schools.